Marshalling water resources: a chronology of irrigation development in the Chi-Mun River Basin, Northeast Thailand - Floch, P.; Molle, Francois (Chiang Mai University, 2007)
Irrigation development in northeast Thailand has witnessed an eventful last century. The 'dry' and 'marginal' lands of northeast Thailand have been continuously reshaped, in an attempt to both balance the seasonality of rainfall and to counter the in-season variations that constrains rainfed cultivation. Apart from that, the Thai government's support for irrigation development has served many additional goals: food security and self-sufficiency, the creation of rural employment opportunities along with the support of agribusiness development, a counterstrategy against migration to the rural and national economic centers, and the fight against insurgency and the spread of communism. Throughout this period, attempts to render nature fit for human use has been both a state and a local process. Years before the height of the hydraulic mission in Thailand, farmers and communities have diverted surface waters with earthen bunds, constructed water wheels, and scooped water from channels and ponds to supplement water for agricultural production. While mostly local in the early years of the 20th century, it was only in the 1950s, both with the advent of the states increasing attempts to draw the peripheries of Thailand closer to the central state of (then) Siam, and with international aid flowing in for water resources development, that state sponsored irrigation development started to shape the waterscape of the region. First small in scale, these developments soon turned to large and multipurpose projects, and to a regionalization of water planning and development, which (at least on paper) interconnected the river basins of northeast Thailand. Interbasin-diversion (mostly from the Mekong main stem and more recently from Laos) to supplement the regions low runoff and limited available storage sites have rationalized the expansion of irrigated areas and have triggered dreams of a "Green Northeast?, an area where most agricultural land would be served by irrigation infrastructure. We will here, revisit irrigation developments in Northeast Thailand in an attempt to periodize changes in the major schools of thought and the dominant ideologies pushing for changing water resources development options, the major impacts of these developments which in turn influenced the considered options, and the economics of irrigation development at large. Furthermore, we will propose a trajectory of irrigation development in the Chi-Mun river basin, which, linking with the proposed storyline, will quantify the developments in the last century. Through this exercise we will highlight changes in land and water use, and trace major paradigms of water resources development back to their roots.